PENGARUH SERVANT LEADERSHIP DAN BUDAYA ORGANISASI TERHADAP OCB DIMEDIASI OLEH KEPUASAN KERJA PADA PT. PUPUK ISKANDAR MUDA CABANG MEDAN - Febryansyah, T. Mohd; Setiawan, Teguh; Ritonga, Ilham Mubaraq (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to determine the effect of servant leadership and organizational culture on job satisfaction, to determine whether job satisfaction mediates the effect of servant leadership and organizational culture on organizational citizenship behavior (OCB) at PT. Pupuk Iskandar Muda Medan Branch. The population in this study was 130 respondents and using saturated sampling techniques. The analysis technique used is path analysis. The results of the study indicate that servant leadership has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, servant leadership has a positive and significant effect on OCB, organizational culture has a positive and significant effect on OCB, job satisfaction has a positive and significant effect on OCB, job satisfaction significantly mediates the effect of servant leadership on OCB and job satisfaction significantly mediates the effect of organizational culture on OCB at PT. Pupuk Iskandar Muda Medan Branch.